Clinical, Histologic and Histomorphometric Evaluation of Bone Strip Allograft with Resorbable Membrane in Horizontal Alveolar Ridge Augmentation: A Preliminary Study - Amooian, Babak; Seyyed Majidi, Maryam; Haji Ahmadi, Mahmoud; Kiakojouri, Amir (Journal of Dental School, 2019)
Objective: Alveolar ridge preservation in patients with inadequate bone volume is one treatment option for successful implant placement and can be done by using bone graft materials. On the other hand, Ceno Bone has been recently produced by Hamanand Saz Baft Kish Co. as a bone bioimplant of allograft origin. This study aimed to assess the clinical, histologic and histomorphometric results of Bone Strip Allograft (CenoBone) for horizontal alveolar ridge augmentation. Methods: In this semi-experimental clinical trial, 7 areas requiring horizontal ridge augmentation and subsequent implant placement in the maxilla were selected using non-randomized consecutive sampling. Surgeries were mostly performed via the buccal cortical plate of the edentulous ridge. The buccal bone was decorticated, Ceno Bone was fixed by titanium screws, covered with Ceno Membrane (resorbable) and sutured. Buccolingual width of the ridge was measured in stage-one surgery and six months later in stage-two surgery for implant placement. A core biopsy was also taken to assess the trabecular thickness, percentage of new bone formation, percentage of remnant particles, degree of inflammation, foreign body reaction, vitality, bone-biomaterial contact and number of blood vessels by microscopic, histologic and histomorphometric analyses of the slides. The clinical ridge width values in the first- and second-stage surgeries were analyzed using Wilcoxon Signed Rank test. Results: The mean clinical ridge width at 2mm distance from the ridge crest was 2.49 (0.72) mm in the first-stage and 4.79 (0.75) mm in the second-stage surgery. The mean clinical ridge width at 5mm distance from the ridge crest was 3.6 (0.57) mm in the first-stage and 6.3 (1.13) mm in the second-stage surgery. At both sites, application of Ceno Bone significantly increased the clinical ridge width in the second-stage surgery (both ps<0.05). Also, inflammation in most specimens (85.7%) was grade I and no case of foreign body reaction was seen. Bone was vital in all patients. The mean trabecular thickness was 87.96 (38.74)μ. The percentage of new bone formation was 58.43 (26.42%) and the percentage of remnant particles was 4.07% (2.44%). Conclusion: The results of this preliminary study revealed that application of CenoBone stimulates osteogenesis and significantly increases the clinical ridge width at 2 and 5mm distances from the ridge crest for implant placement.